Water Pollution and Its Health Impacts on Humans: Understanding the Health Consequences of Water Pollution (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Water is renewable but its renewable takes time. In these days, water quality is constantly degrading due to urbanization, industrialization, population explosion and many more reasons. Water pollution can occur on account of any one or more of the agents like biological agents, chemical agents and physical agents. Chemical characteristics of water is explained with the help of many physico-chemical parameters viz. pH, Na+, K+, Ca2+, Mg2+, SO42–, CO32–, HCO3–, TH, Cl–, NO3–, Oil Grease, Fluoride, etc. Some of them are within permissible limits and some of them are in contamination limit. Many of heavy metals like arsenic, mercury, lead, cadmium, copper, etc. are at alarming levels in drinking water and causes many health issues. This paper emphasizes on many health issues due to water pollutants which are at high concentration in the potable water.